PERLINDUNGAN HUKUM TERHADAP KONSUMEN PT OVO FINANCE INDONESIA SETELAH IZIN USAHA DICABUT OLEH OTORITAS JASA KEUANGAN - Arta Dian Sopinta Maruao; Lesson Sihotang; Debora (Magister Hukum Universitas HKBP Nommensen, 2024)
A finance company is a company that provides goods or capital needed by the community through cooperation with companies that provide goods referred to by a gradual payment mechanism. Therefore, finance companies have a great responsibility for the fulfillment of consumer rights when entering into agreements, for example in the use of consumers' personal data and information. PT Ovo Finance Indonesia, which is a finance company that has been revoked its business license by the Otoritas Jasa Keuangan in October 2021. This business license revocation event brought a serious polemic to the legal protection of the rights and obligations of its consumers. In an effort to provide legal protection, it will be divided into two types, namely preventive legal protection and repressive legal protection. In this study, we will discuss and understand the scope of the condition of the company PT Ovo Finance Indonesia after its business license is revoked by the Otoritas Jasa Keuangan and how to legally protect the rights and obligations of its consumers. Therefore, to answer this formulation, researchers conduct research using normative legal methods and descriptive qualitative. Researchers will trace and review laws regulations to then be able provide an overview of the subject matter that occurs.